Acute cholangitis detected ectopic ampulla of Vater in the antrum incidentally: A case report - Lee, Hsu-Lin (World J Clin Cases, 2021)
BACKGROUND: The ampulla of Vater is an opening at the confluence of the common bile duct and pancreatic duct. It is located in the second portion of the duodenum. An ectopic papilla of Vater is an anomalous termination. Few cases have been reported. We report the rare case of a man with an ectopic ampulla of Vater in the pylorus. CASE SUMMARY: An 82-year-old man had experienced abdominal pain and fever with chills 1 d before his presentation. A computed tomography scan of the abdomen demonstrated dilatation of the common bile duct approximately 2.2 cm in width. Gas retention was found in his intrahepatic ducts. Acute cholangitis with pneumobilia was identified, and he was hospitalized. Esophagogastroduo-denoscopy and endoscopic retrograde cholangiopancreatography disclosed no ampulla of Vater in the second portion of the duodenum. Moreover, a capsule-like foreign body (pharmaceutical desiccant) approximately 1 cm × 2 cm in size was found at the gastric antrum and peri-pyloric region. After the foreign body was removed, one orifice presented over the pyloric ring in the stomach, a suspected ectopic ampulla of Vater. Subsequently, sludge in the common bile duct was cleaned, and balloon dilatation was performed. The general condition improved daily. The patient was discharged in a stable condition and followed in our outpatient department. CONCLUSION: This case involved an ampulla of Vater in an unusual location. Endoscopic retrograde cholangiopancreatography with balloon dilatation is the main treatment recommended and performed.